The Effect of Snowball Throwing Cooperative Learning Model on Student Learning Outcomes in Class VII Private Junior High School Teladan Pematang Siantar T.A 2022/2023 - Theresia Tiara Br Tondang; Debbi Petra Meyana Sitorus; Injen Pardamean Butarbutar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of the snowball throwing cooperative learning model on student learning outcomes in social studies class VII at Teladan Private Middle School Pematang Siantar T.A 2022/2023. The study used a quasi-experimental method (quasi-experimental) with the Nonequivalent Control Group Design. This design consists of two stages, namely pretest and posttest. The sample in the study in class VII was 22 students and VII-2 was 22 students. The research instrument used was the learning achievement test. From the results of the analysis carried out in the experimental class with an average pretest score of 49.95 and a posttest of 70.68. While in the control class with an average pretest score of 50.23 and a posttest average score of 52.73. The results of testing the hypothesis using an independent sample t-test obtained tcount 4.941 > ttable 1.684 and a significance of 0.000 <0.005 so that it can be concluded that student learning outcomes are taught using the snowball throwing cooperative learning model which is influential and well used in learning.